ANALISIS MATERI AKHLAK PADA KITAB HADITS ARBA'IN AN-NAWAWI DALAM PENANAMAN NILAI-NILAI KARAKTER SISWA DI SMP SYEKH ABDURRAHMAN RABAH PADEMAWU PAMEKASAN - Moh Beni Pratama; Zainol Hasan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the content of moral material in the Hadith of Arba'in An-Nawawi and analyze its implementation in the formation of character values of students at Syekh Abdurrahman Rabah Pademawu Pamekasan Middle School. The focus of the study is directed at strengthening three main character values, namely religious, discipline, and respect (takzim). The study uses a qualitative approach with a descriptive research type. Data were obtained through observation, in-depth interviews with the principal, Islamic Religious Education teachers, and students, as well as documentation studies of learning tools. Furthermore, the data were analyzed using the Miles and Huberman interactive model which includes data reduction, data presentation, and drawing conclusions. The validity of the data is guaranteed through the application of source triangulation and technical triangulation. The results of the study indicate that the Hadith of Arba'in An-Nawawi contains moral values that cover three main aspects, namely morality towards Allah SWT, morality towards oneself, and morality towards fellow human beings. The implementation of this material is carried out through routine study and memorization of hadith, the instilling of Islamic behavior in daily life at school, and the role model provided by teachers and the principal. Through this process, students demonstrate the development of religious character, discipline, and respect (takzim), which are reflected in their behavior during learning activities and at school. Successful implementation is supported by the school's commitment, teacher competence, a religious learning environment, and parental involvement in character development. Challenges encountered include limited learning time, the influence of digital media use, and suboptimal character building within the family environment. Based on the research results, it can be concluded that the implementation of the moral material in the Hadith of Arba'in An-Nawawi plays a crucial role in shaping students' character through a continuous process of learning, habituation, and role modeling within the school environment.